Projecting trends in the disease burden of adult edentulism in China between 2020 and 2030: a systematic study based on the global burden of disease - Qin, Xiaofeng; Chen, Li; Yuan, Xihua; Lin, Dan; Liu, Qiulin; Zeng, Xiaojuan; Ma, Fei (Frontiers in Public Health, 2024)
This study was based on the Global Burden of Disease (GBD) database and aimed to analyze the trend of disease burden for complete edentulism in Chinese adults between 1990 and 2030, and to provide valuable information for the development of more effective management and preventive measures.Data on Chinese adults with complete edentulism from 1990 to 2019 was analyzed using GHDx data. Descriptive analyses were used to analyze changes in the prevalence and burden of complete edentulism, gender and age distribution between 1990 and 2019. In addition, we used an autoregressive integrated moving average (ARIMA) model to predict the trend of disease burden for Chinese adults with complete edentulism between 2020 and 2030.